Studies of Asilidae (Diptera) systematics and evolution: II. The tribes of Dasypogoninae - Papavero, N. (Arquivos de Zoologia, 1973)
The Asilidae subfamily Dasypogoninae is divided in 5 tribes: Blepharepiini (1 genus), Lastaurini (11 genera), Isopogonini (16 genera), Megapodini (8 genera), and Dasypogonini (34 genera). A brief diagnosis of the tribes, a list of their genera, their distribution, and a speculative history of their phylogeny in the light of the present knowledge of continental drift, are given.